2009
DOI: 10.1021/cm9012443
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Symmetry on the Stability of Columnar Liquid Crystals

Abstract: To assess the effects of molecular symmetry on the phase transitions of columnar liquid crystals, we prepared a family of 19 discotic mesogens. This series of dibenzophenazine derivatives allowed us to compare the differences in phase transitions between sixteen pairs of isomers that differed in terms of their overall symmetry. It was found that the more symmetrical isomer had a significantly higher melting temperature in all but one case, whereas symmetry appeared to have a lesser impact on clearing temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 40 publications
2
32
1
Order By: Relevance
“…Comparing the mesomorphism of 2,7‐diaryl‐TPs D 1 , D 2 , and D 4 with those of their 2,3‐ and 3,6‐isomers, the most influential structural features for the induction and stabilization of mesomorphism is the larger separation between both substitution positions rather than the molecular symmetry alone. For example, the 2,7‐ and 3,6‐isomers, which favor a more homogeneous distribution of the aliphatic continuum between the columns, are less perturbed than they would be if the substituents were closer to each other, as in the 2,3‐isomer , …”
Section: Resultsmentioning
confidence: 99%
“…Comparing the mesomorphism of 2,7‐diaryl‐TPs D 1 , D 2 , and D 4 with those of their 2,3‐ and 3,6‐isomers, the most influential structural features for the induction and stabilization of mesomorphism is the larger separation between both substitution positions rather than the molecular symmetry alone. For example, the 2,7‐ and 3,6‐isomers, which favor a more homogeneous distribution of the aliphatic continuum between the columns, are less perturbed than they would be if the substituents were closer to each other, as in the 2,3‐isomer , …”
Section: Resultsmentioning
confidence: 99%
“…In this context, varying the exible chains that surround the aromatic core is particularly attractive because changes in chain length, branching and pendant functional groups all strongly impact phase behaviour. 3 However, relatively few studies have explored the effects of this kind of side chain shuffling, 4-12 likely due to the challenges associated with regioselectively preparing discotic mesogens bearing several different chains. For example, we have shown that swapping the positions of the hexyloxy and decyloxy chains from 1 to 2 ( Fig.…”
mentioning
confidence: 99%
“…3 The same generalization does not apply to the clearing temperatures. This is consistent with our earlier observation that reducing the molecular symmetry tends to depress the crystalto-columnar transition temperature within a series of isomers.…”
mentioning
confidence: 99%
“…To balance these competing parameters, rod–coil molecules self‐organize into a diverse supramolecular structures, which can be controlled by tuning of the rod to coil volume fraction, the number of grafting sites per rod, rod anisotropy, coil cross‐sectional area and incorporating the side groups into a rod block . The self‐assembling behavior of rod–coil copolymers based on various shapes of rod building block including Y‐shaped, T‐shaped, O‐shaped, K‐shaped, propeller‐shaped, and dumbbell‐like have been reported by Percec, Lee, and other research groups . The ordered nanostructures of rod–coil molecules have been created by introduction of diverse flexible coil segments into the various shaped rod building block and produce unique self‐assembling or aggregation structures .…”
Section: Introductionmentioning
confidence: 99%